(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The learning model is one of the important components in learning. The learning model needs to be developed because the learning model can provide useful information for students. Learning will be effective if it is carried out in a pleasant atmosphere, therefore the choice of methods, strategies and approaches in designing learning models must be created by the teacher so that an active, creative, effective and enjoyable atmosphere is created. One learning model that needs to be applied to actively involve students is the Virtual Education learning model. In this learning, students will indirectly learn to understand the material provided by the teacher and it is hoped that learning like this can be fun and students are more active in teaching and learning activities so that it is expected to improve learning outcomes. According to Dimyati Mudjiono (2006: 3-4) learning outcomes are the result of an interaction of learning and teaching actions. So it can be concluded, learning outcomes are abilities obtained by a student after going through learning activities for a certain period teach.